Carcass Color in Broilers When Replacing Wheat with Corn in the Diet - Maria del Mar Campo; Leticia Mur (Foods)
The effect of replacing wheat with corn on the color distribution across various locations in the carcasses of broilers was assessed. One thousand two hundred ROSS 308 one-day-old male chicks were reared in an experimental farm, with ten pens per treatment, based on the primary cereal ingredient during both the starter (1–14 d) and grower (15–41 d) phases: corn and wheat. At 41 days old, slaughtering was performed. At 24 h post slaughter, color measurements were taken in 15 carcasses per treatment using a MINOLTA CM600d reflectance spectrocolorimeter in the CIEL*a*b* space. Twelve locations were measured: drumette, apterial latero-pectoral area, neck, the back at the seventh thoracic vertebra, saddle, thigh, ham, hock and around the vent, shanks, and the surface and interior of the breast. The results indicate that the color distribution in the broiler carcass is not homogeneous. Very small color differences can be found between the surface and the interior of the breast, but they differ greatly from areas where there is skin. Corn produces a darker color than wheat, though the intact skin homogenizes lightness* across the entire carcass, reducing differences between regions. Corn increased mainly yellowness, influencing color saturation. The pronounced color differences between the shank and other locations almost disappear when corn is excluded from the feed. Hue° could serve as a potential indicator of color variations in the breast resulting from differences in dietary ingredients.